Upaya Keluarga, Masalah Gizi, Ba UPAYA KELUARGA DALAM PENANGANAN MASALAH GIZI BALITA SELAMA PANDEMI COVID 19 - Khoirunissa, Indah; Asiyah, Siti; Setyarini, Arika Indah (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
One of the unresolved health problems in Indonesia is the problem of malnutrition in children under five. Due to the emergence of the COVID 19 pandemic around the world, the number of children under five who are malnourished, malnourished, and stunted is increasing. The impact of malnutrition is very complex, children can experience mental, social, cognitive and growth development disorders. The purpose of this study is to find out what are the family's efforts in handling the nutritional problems of toddlers during the covid 19 pandemic. The design used is Traditional Review, Journals articles are derived from searches of 4 databases, namely Google Scholar, ResearchGate, ProQuest, Litcovid using related keywords. The solution is taken by paying attention to the PEOS framework, then analyzed one by one. The review shows that there are 7 family efforts in handling nutritional problems. The majority of the efforts made by the family are detection of growth and development through social media whatsapp groups. Efforts to detect growth and development are mostly given by families to deal with the problems of undernutrition, malnutrition, and stunting in toddlers. These efforts must also be developed according to the conditions so that the services provided are right on target.